2010
DOI: 10.1510/icvts.2009.220319
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing and placing a bespoke support for the Marfan aortic root: description of the method and technical results and status at one year for the first ten patients

Abstract: Fatal aortic dissection commonly occurs in Marfan syndrome. Prevention currently relies on elective replacement of the aortic root. We are evaluating the placement of a manufactured, bespoke external support derived from a computer aided design in a prospective study. In the first ten patients, measurements were made consistently of the ascending aorta at the level of closure of the aortic valve cusps from magnetic resonance imaging (MRI) studies taken preoperatively and at fixed intervals thereafter. Before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 13 publications
1
45
0
1
Order By: Relevance
“…Early clinical results of PEARS indicated that there is no further dilatation of the aortic root after insertion of the PEARS, although the long term outcome cannot be predicted based on such early and limited experience [11,12]. Additionally, the structural status of the aortic wall after PEARS is uncertain [13].…”
Section: Introductionmentioning
confidence: 99%
“…Early clinical results of PEARS indicated that there is no further dilatation of the aortic root after insertion of the PEARS, although the long term outcome cannot be predicted based on such early and limited experience [11,12]. Additionally, the structural status of the aortic wall after PEARS is uncertain [13].…”
Section: Introductionmentioning
confidence: 99%
“…Основной целью было стремление избежать назначения антикоагулянтов, обязатель-ных после протезирования АоК с использованием механического клапана [2,4,6,7]. Однако вероят-ность дисфункции клапана и необходимость реопе-рации были неизвестны.…”
Section: Long-term Results Of the Valve-saving Surgery In Marfan Syndunclassified
“…Interestingly enough in this model the endovascular net prosthesis provides aortic wall mechanical support just where the mechanical stress is higher (Robicsek & Thubrikar, 1994) ( fig. 25), and thus just where it's most needed both to prevent further dilatation, theoretically preventable also by external aortic wall wrapping (Pepper et al 2010), and to avoid partial (dissection) or total rupture, with optimization of the amount of prosthetic material. The reduced volume of the net prosthesis in comparison with current endoprosthesis (≤1/6 th approximately) further greatly enhances its introduction through peripheral vessel often tortuous and restricted by atherosclerosis.…”
Section: The Rationalmentioning
confidence: 99%
“…26. However fluid-dynamic shapes of the net threads will be also evaluated in mechanical models with the aim to verify if it is possible to achieve conduit inner wall contact by means of pure fluid stream  Ascending aorta and Arch require variably curved net prosthesis ( fig 26, right); for these tracts however bespoke prosthesis on the individual TC scan, maybe with wider meshes for the supraortic trunks area, is an option to be considered for clinical use; bespoke prosthesis however have being already realized in a external ascending aorta wrapping protocol (Pepper et al, 2010)).  Endovascular delivery system is also to be realized The nitinol wireframe adds to the net further structural strengthening then greatly exceeding that required; an accurate structural mechanics computation would theoretically allow the achievement of the necessary aortic wall structural strengthening to permanently fix aortic diameter with really a very thin and wide meshes net prosthesis.…”
Section: Ideal "Net" Prosthesis Prototypes Setupmentioning
confidence: 99%